AI CHATBOT FOR MENTAL HEALTH - Kiruthika, R.; Ajay, R.; Balakrishnan, P.; Giridharan, S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Modern artificial intelligence (AI), and machine learning in particular, is being utilized to develop prediction, detection, and treatment solutions for mental health care with the emergence of digital approaches to mental health. AI is being used in therapy to improve user experience and maximize individualized mental health care through digital interventions, including web and smartphone apps. Modern sources of copious amounts of data allow for the development of prediction/detection models for mental health disorders through the use of data-driven AI techniques. Specifically, behavioral or mental health insights can be extracted from an individual's "digital exhaust," which is the data obtained from their multiple personal digital devices and social media activities. Language has traditionally been seen as a window into the human mind, but with the help of potent computer-based natural language processing, it can now be statistically used as data to infer mental health. Furthermore, conversational agents for therapeutic intervention can be created using natural language processing